PENGARUH KARAKTERISTIK DIREKTUR UTAMA TERHADAP PENGHINDARAN PAJAK PERUSAHAAN MANUFAKTUR DI INDONESIA TAHUN 2020 – 2024 - Salfa Syaharani; Edy Supriyono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This research aims to explore the relationship between CEO characteristics and tax avoidance behaviour of publicly traded manufacturing firms in Indonesia Stock Exchange (IDX) over a three year period from 2020 to 2024. Four important areas of investigation for this study include: (1) age of CEO; (2) sex/gender of CEO; (3) education level/background of CEO; and (4) length of time serving as CEO. A quantitative methodology was applied using multiple regression on a panel data set containing 250 firm level observations. Findings revealed that the education level and time served as a CEO were significantly and positively correlated with tax avoidance behaviour while both age and gender were not determined to statistically impact tax avoidance behaviour.  These findings provide direct implications for tax authorities and corporations to consider with respect to how corporate executive characteristics impact tax strategy decisions. Keywords: Tax Avoidance, President Director, Educational Background, Tenure, Executive Characteristics.